2014
DOI: 10.1590/s0100-06832014000400024
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of soil hydraulic properties under a long term no-till system

Abstract: SUMMARYThe area under the no-tillage system (NT) has been increasing over the last few years. Some authors indicate that stabilization of soil physical properties is reached after some years under NT while other authors debate this. The objective of this study was to determine the effect of the last crop in the rotation sequence (1 st year: maize, 2 nd year: soybean, 3 rd year: wheat/soybean) on soil pore configuration and hydraulic properties in two different soils (site 1: loam, site 2: sandy loam) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
12
0
3
Order By: Relevance
“…However, cases where the above-mentioned natural stabilization of soil properties are not uncommon as a natural soil compaction was reported even at the end of an annual growth cycle [67,73]. Past this time, if a soil is no longer tilled, the literature agrees that the above-mentioned natural stabilization of soil properties may occur after about five to six years [17,76].…”
Section: Discussionmentioning
confidence: 98%
“…However, cases where the above-mentioned natural stabilization of soil properties are not uncommon as a natural soil compaction was reported even at the end of an annual growth cycle [67,73]. Past this time, if a soil is no longer tilled, the literature agrees that the above-mentioned natural stabilization of soil properties may occur after about five to six years [17,76].…”
Section: Discussionmentioning
confidence: 98%
“…The increase of u ma toward AH could be attributed to the crop. The maize roots are strong and create continuous macropores (Fahad et al, 1982;Bathke and Blake, 1984;Lozano et al, 2014). Then, the increase on u ma from BS to V6 can be attributed to the decay of the roots of the previous crop (maize) during the studied season.…”
Section: Temporal Variation Of S Posd and Kmentioning
confidence: 97%
“…However, other authors found that soil physical properties vary temporally under NT. Lozano et al (2014) found that after a long period under NT, the porous system configuration and K of a Argiudoll from the pampas region did not reach steady values, regardless of the specific time in the crop sequence. Moreira et al (2016) concluded that soil physical properties under NT vary during the crop growing season.…”
Section: Introductionmentioning
confidence: 93%
“…The increase in ε ma and ε me from BS to V6 can be attributed to decay of the roots of the previous crop (corn) during the season studied. Corn roots have been reported to create vertical macropores (Lozano et al, 2014). The decrease in K 0 and in pore size fractions and connectivity in AH can be attributed to the high traffic intensity associated with harvest (Soracco, 2009;Soracco et al, 2012).…”
Section: Rev Bras Cienc Solo 2018;42:e0170408mentioning
confidence: 99%
See 1 more Smart Citation